Job satisfaction and its demographic, occupational, and mental health determinants among community pharmacists - Anan S. Jarab; Ahmad Z. Al Meslamani; Walid Al-Qerem; Hamza Jarab; Eman Merghani Ali Mohammed; Hebatallah Ahmed Mohamed Moustafa; Abdallah Y. Naser; Yazid N. Al Hamarneh; Salahdein Aburuz (PLoS ONE, 2026)
Background Job satisfaction among community pharmacists influences service quality, patient outcomes, and workforce stability, yet evidence from Jordan is limited and fragmented. Objectives To determine the overall level of job satisfaction among Jordanian community pharmacists and examine its associations with demographic, occupational, and mental-health factors. Methods A cross-sectional study was among licensed community pharmacists working in independent and chain pharmacies across Jordan. Data were collected using a validated, self-administered online questionnaire distributed through convenience sampling. The survey included items on demographic and occupational characteristics, as well as three validated mental health scales: the Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and Perceived Stress Scale-10 (PSS-10). Job satisfaction was assessed using a single-item global question. A binary logistic regression analysis was conducted to explore the variables associated with job satisfaction among participants. Results Among 385 respondents, 257 (66.8%) pharmacists reported being satisfied with their job. Satisfied pharmacists handled more patients per shift (median 150 [IQR 100–250] vs 150 [40–200]; p = 0.050), filled more prescriptions (60 [30–90] vs 50 [24–90]; p = 0.042), and dispensed more medications (200 [100–300] vs 175 [57.5–300]; p = 0.028). In multivariable analysis, fixed-evening (AOR 0.46, 95% CI 0.22–0.95) and flexible shifts (AOR 0.41, 95% CI 0.19–0.89) reduced satisfaction odds, whereas each additional patient handled slightly increased satisfaction odds (AOR 1.004, 95% CI 1.001–1.008). Conclusion Mental-health symptom burden and most demographic factors are unrelated to satisfaction, whereas workload patterns, particularly shift timing and patient volume, exert significant influence. Optimising shift assignments and staffing to balance high patient engagement with manageable hours may enhance pharmacist retention and care quality.